Five new species of Utetes Foerster (Hymenoptera, Braconidae, Opiinae) from NW China - Tan, Jiang-Li; van Achterberg, Cornelis; Zhang, Ruo-Nan; Wu, Jia-Xuan (Zootaxa, 2018)
Five new species of the genus Utetes Foerster, 1863 (Hymenoptera, Braconidae, Opiinae) are reported from Shaanxi and Ningxia provinces (NW China). The new species (U. aharmus sp. n., U. elongisulcus sp. n., U. karsius sp. n., U. stenotus sp. n. and U. subrosae sp. n.) are keyed and fully illustrated. Opiognathus pratensis (Weng & Chen, 2005) comb. n., Apo-desmia punctata (Chen & Weng, 2005) comb. n. and Phaedrotoma saltator (Telenga, 1950) comb. n. are new combinations.